Identification and Determination of concentrations of some Toxic alkaloids in Jimsonweed (Datura stramonium L.) - MOHAMED, EHAB ELSIR; Hassan, Nasma A.A.; Khalid, Almoiz E.M. (Gezira Journal of Agricultural Science, 2021)
Alkaloids are regarded as complex naturally occurring products of plants and fungi. They possess nitrogen-containing heterocyclic rings, basic and derived from amino acids. High physiological activity is also a characteristic of alkaloids. This study was aimed to determine the existence and concentrations of some toxic alkaloids in different parts of jimsonweed ( Datura stramonium L.) of the family Solanaceae. Stems, leaves and fruits were dried, crushed and then underwent extraction. Solvents used in the extraction were chloroform and acetic acid. Thin layer chromatography (TLC) and GC-MS techniques were also adopted in analyzing the alkaloids. The results revealed the presence of atropine in stems, leaves and fruits of D. stramonium with concentrations of 0.03, 0.4 and 0.08 mg/g, respectively. Hyoscine was also found in stems, leaves and fruits with concentrations of 0.01, 0.02 and 0.2 mg/g, respectively. Nicotine was found in stems and fruits with concentrations of 0.001 and 0.02 mg/g, respectively. This study showed and provided the possibility of exploring new natural potential pesticides from Sudanese indigenous plants and provide important information to avoid toxicity, harmful and adverse effects of these plants to both humans and animals.